Capturing motivation and emotion regulation during a learning process - Hanna Järvenoja; Sanna Järvelä; Tiina Törmänen; Piia Näykki; Jonna Malmberg; Kristiina Kurki; Arttu Mykkänen; Jaana Isohätälä (EARLI, 2018)
This paper describes our research approach in which we have focused on situational and contextual variations in motivation and emotion regulation to better understand its role, appearance and function in collaborative learning situations. We have used research designs that employ process-oriented measures combined with subjective interpretations to capture motivation and emotion regulation. Analysing on-line process data poses several challenges such as variation in the granularity of different data sources, problems that emerge due to the complexity of contextual and situational factors in ecologically-valid learning situations or, currently, challenges in the use of multiple data channels and their analyses. In this paper, we present three claims underlying our research, particularly the motivationand emotions and their regulation in learning. The claims are as follows: (1) motivation and emotion regulation is situation and context specific, (2) motivation and emotion regulation is influenced by multi-layered nature of motivationand(3) Motivation and emotion regulation is intertwined with other processes of learning and can be captured from their temporal manifestation. We present an example from our empirical study to discuss how these claims have led us to employ multiple process-oriented methods that include both subjective and objective data sources, including different combinations of situation-specific self-reports, video and physiological data. We then describe opportunities and challenges involved in the empirical studies.